Genome‐Wide Association Mapping of Grain Mold Resistance in the US Sorghum Association Panel. Issue 2 (1st June 2019) - Cuevas, Hugo E.; Fermin‐Pérez, Ramon A.; Prom, Louis K.; Cooper, Elizabeth A.; Bean, Scott; Rooney, William L.
Abstract : Sorghum [ Sorghum bicolor (L.) Moench] production in warm and humid regions is limited by grain mold disease, which can be caused by a complex of >40 pathogenic and opportunistic fungi. The identification of resistant plants within temperate‐adapted germplasm is imperative for the development of better‐adapted varieties. The performance of 331 accessions from the previously genotyped sorghum association panel (SAP) was evaluated in four tropical environments. Only 18 accessions showed low seed deterioration and high emergence rates. The resistant accessions showed high variation in seed tannin contents and panicle shape, indicating that grain mold resistance is not associated with a single phenotypic trait. Seed mycoflora analysis recovered pathogenic fungi Curvularia lunata, Fusarium thapsinum, and F. semitectum in both resistant and susceptible accessions. By genome‐wide association scans using 268, 289 single nucleotide polymorphisms (SNPs), we identified two loci associated with low seed deterioration and another associated with emergence rate. Candidate genes within these loci included one R gene ( Sobic.08G132000 ) and two genes ( Sobic.01G349300 and Sobic.10G222400 ) with domains associated with systemic acquired resistance, suggesting that resistance involved pathogen recognition and downstream signaling cascades. This study provides insight into the genetic control of grain mold resistance as well as valuable accessions for breeding programs in temperate environments.